Precision Nitrogen Management in Wheat at Rampur, Chitwan, Nepal (Journal of Agriculture and Environment, 2022)
The application of blanket recommendation of nitrogen fertilizer leads to over or under fertilization. There is need to synchronize the N fertilizer application with plant demand.  Field experiment was conducted during 2019 -2020 in Chitwan to assess the yield, nitrogen use efficiencies and economics of wheat production under precision N management compared with fixed time N management. Experiment was laid out in split plot design with sixteen treatments and three replications. The main plot treatments were varieties Vijay and Banganga and subplot treatments were three SPAD readings (≤35, ≤40, ≤45), two LCC readings (≤4, ≤5), Nutrient expert tool, fixed time nitrogen management(FTNM) with national recommended dose and control (zero N). The research result showed that varieties did not differ in yield and economics. Precision nitrogen management with SPAD≤45 and LCC≤5 consumed higher nitrogen doses and produced better yield attributes and yield (5585 and 5385 kgha-1 respectively) compared with FTNM. The agronomic use efficiency of nitrogen (AEN), recovery efficiency (REN), partial factor productivity (PFP were highest at LCC≤4 which consumed less nitrogen. SPAD≤35, LCC≤4 and NE treatments saved 15, 35 and 20 kgha-1 N respectively without compromising the yield obtained in FTNM. But, the benefit: cost ratio was highest at LCC≤5.Therefore, in terms of yield and profitability of wheat production, LCC≤5 is better than other treatments. The present national recommended dose of nitrogen to wheat crop is insufficient to achieve higher yield in Chitwan condition.